(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdbSe GdKGfj ef GdCbSGe GdCQHYI GdJj Hfj YdjgG GdcJGH aj GdYbhO, LeY YbO hgh dZI VO GdMd hTQYG bhd ef GdeJYGbOjf Ch bhd ef CMOgeG hbjd ef GdCNjQs
(3BNQgG (B:s
(3BNQgG(B: (3hjfHZj JbOje TOjO GdMGLI Ydi ZjQg aj GdHjY, Hd bO jLH eY GdBVWQGQ hEf UM GdHjY eY GdeNGdaI hdh cGf (B.. (3SO LHQI GdeLJgO GdBNQ hEf cGf eaVhdG aEf de jcf (B... (3hGddg gh GdYGde HMbjbI CMcGegs
(3GdfSNI ebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis